Numerical investigation of symmetry breaking and critical behavior of the acoustic streaming field in high-intensity discharge lamps. (27th May 2015) - Baumann, Bernd; Schwieger, Joerg; Wolff, Marcus; Manders, Freddy; Suijker, Jos
Abstract: For energy efficiency and material cost reduction it is preferred to drive high-intensity discharge lamps at frequencies of approximately 300 kHz. However, operating lamps at these high frequencies bears the risk of stimulating acoustic resonances inside the arc tube, which can result in low frequency light flicker and even lamp destruction. The acoustic streaming effect has been identified as the link between high frequency resonances and low frequency flicker. A highly coupled three-dimensional multiphysics model has been set up to calculate the acoustic streaming velocity field inside the arc tube of high-intensity discharge lamps. It has been found that the velocity field suffers a phase transition to an asymmetrical state at a critical acoustic streaming force. In certain respects the system behaves similar to a ferromagnet near the Curie point. It is discussed how the model allows to investigate the light flicker phenomenon. Concerning computer resources the procedure is considerably less demanding than a direct approach with a transient model.